2019
DOI: 10.4236/ojbiphy.2019.91003
|View full text |Cite
|
Sign up to set email alerts
|

Effective-Spring Model of Tympanic Response in Archosaurs

Abstract: Whereas for smaller animals the eardrums are well-characterized as excitable membranes or drums, some animals such as several archosaurs feature, as a first approximation, a rather stiff elastic shell supported by an elastic ring. Mathematically, the theory of plates and shells is applicable but its governing equations overly complicate the modeling. Here the notion of tympanic structure is introduced as a generalization of "ordinary" tympanic membranes so as to account for sound perception as it occurs in arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The general provisions connected with the middle ear and drum membrane mechanics are described in the overview work [23], where it is demonstrated that the drum membrane can be interpreted as a mechanical membrane. In [24], the authors propose the system of two ordinary differential equations as a model of drum membrane oscillations, and the solution of this system is defined by an integral operator. The drum membrane model was examined and the probabilistic estimate of breakout risk as an explosion result was calculated in [25].…”
Section: Oscillations Of Circular Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…The general provisions connected with the middle ear and drum membrane mechanics are described in the overview work [23], where it is demonstrated that the drum membrane can be interpreted as a mechanical membrane. In [24], the authors propose the system of two ordinary differential equations as a model of drum membrane oscillations, and the solution of this system is defined by an integral operator. The drum membrane model was examined and the probabilistic estimate of breakout risk as an explosion result was calculated in [25].…”
Section: Oscillations Of Circular Membranesmentioning
confidence: 99%
“…In article [24], the classical equation of forced harmonic vibrations without friction is considered as a simplified vibration model. So, if in our case for Equation (1) we take Lu = F f ull and assume that the solution u depends only on time, then for α 2 (t) = m, β(t) = 0, γ 2 (t) = k, we exactly obtain Equation (8) from this work.…”
Section: Oscillations Of Circular Membranesmentioning
confidence: 99%